Review of soil liquefaction characteristics during major earthquakes of the twenty-first century - Huang, Yu; Yu, Miao (Natural hazards (Dordrecht), 2013)
Liquefaction, which can be defined as a loss of strength and stiffness in soils, is one of the major causes of damage to buildings and infrastructure during an earthquake. To overcome a lack of comprehensive analyses of seismically induced liquefaction, this study reviews the characteristics of liquefaction and its related damage to soils and foundations during earthquakes in the first part of the twenty-first century. Based on seismic data analysis, macroscopic phenomena of liquefaction (e.g., sand boiling, ground cracking, and lateral spread) are summarized, and several new phenomena related to earthquakes from the twenty-first century are highlighted, including liquefaction in areas with moderate seismic intensity, liquefaction of gravelly soils, liquefaction of deep-level sandy soils, re-liquefaction in aftershocks, liquid-like behavior of unsaturated sandy soils. Additionally, phenomena related to damage in soils and foundations induced by liquefaction are investigated and discussed.